Colonel k. Škirpa's suggestion to guarrantee Lithuanian independence by Germany and the Soviet Union and their pledge to support Lithuania in her fight for Vilnius - Linas Locaitis (Lietuvos Istorijos Studijos)
In the 1930's, Colonel Kazys Škirpa served as Lithuania's military attaché in Berlin. His responsibilities included the representation of the Lithuanian Army, development and promotion of friendly relations between Lithuanian and German armies, and collection of information about the German army itself. However, very often during meetings with high-ranking German military staff officers, Colonel K. Škirpa not only discussed political problems that had arisen between Lithuania and Germany, but also spoke of a joint military action against Poland. He attempted to gain support from Germany and the Soviet Union in Lithuania's struggle to regain control of the Vilnius region.